Pelacakan Ekspresi Antigen Toxoplasma gondii secara Imuno(sito)histokimia (TRACKING EXPRESSION OF TOXOPLASMA GONDII ANTIGENS USING IMMUNO(CYTO)HISTOCHEMISTRY METHOD) - Apsari, Ida Ayu Pasti; Winaya, Ida Bagus Oka; Nindhia, Tjokorda Sari; Swacita, Ida Bagus Ngurah (Jurnal Veteriner, 2018)
The research objective want to track the expression of Toxoplasma gondii antigenes in the heart of the free-range chicken with immuno(cyto)histochemistry technique. In the present study were examined three methods to track antigen T.gondii, first method direct microscopic examination of the heart digests, the second method to detect antigen of T.gondii with immunocytochemistry technique of the chicken heart digests and the third immunohistochemistry examination of the heart free-range chicken. The number of material samples examined were 100 heart free-range chicken. Direct microscopic examination of the heart digests free-range chicken to track the bradyzoite form (inside cyst). Examination by immuno(cyto)histochemistry technique keep track T.gondii an antigen expression on cells and heart muscle tissue. The results showed that the direct microscopic examination on the heart tissue unable to detect cyst and antigen T.gondii . Immunohistochemical examination successfully detected the expression of antigenes T.gondii and was found 2% (2/100) positive. It can be concluded that T.gondii antigen expression in the heart of range chicken could be detected by immunohistochemistry.